Hubungan Kewenangan Pemerintah Pusat dan Pemerintah Daerah Dalam Pengawasan Sediaan Farmasi Di Indonesia - Sharon Sharon; Juanda Juanda; Hedwig Adianto Mau (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
The Food and Drug Supervisory Agency (BPOM) is a non-ministerial government agency that carries out government affairs in the field of drug and food control. BPOM is also the organizer of inspection of production facilities and the implementation of inspections of distribution facilities and pharmaceutical service facilities. This research method uses a normative juridical approach, namely a legal approach by looking at regulations, both primary legal materials and secondary legal materials, or an approach to problems by looking at the applicable laws and regulations, books, literature, scientific works. and expert opinion. The results of the study stated that the supervision of pharmaceutical preparations was carried out before they were circulated (pre-market) and during circulation (post-market). The results of this study discuss the relationship between drug control authority in pharmacies and efforts to realize an effective drug control system in pharmacies through harmonization of regulations.Keywords: Pharmacy; Pharmacy Supervision; Government Authority AbstrakBadan Pengawas Obat dan Makanan (BPOM) adalah lembaga pemerintah non kementerian yang menyelenggarakan urusan pemerintahan di bidang pengawasan obat dan makanan. BPOM juga sebagai penyelenggara pemeriksaan fasilitas produksi dan pelaksanaan pemeriksaan fasilitas distribusi serta fasilitas pelayanan kefarmasian. Metode penelitian ini menggunakan pendekatan yuridis normatif, yaitu pendekatan hukum dengan melihat peraturan-peraturan, baik bahan hukum primer maupun bahan hukum sekunder, atau pendekatan terhadap masalah dengan cara melihat dari segi peraturan perundang-undangan yang berlaku, buku-buku, literatur, karya ilmiah dan pendapat para ahli. Hasil penelitian menyatakan bahwa pelaksanaan pengawasan sediaan farmasi dilakukan sebelum beredar (pre-market) dan selama beredar (post market). Hasil penelitian ini, membahas mengenai hubungan kewenangan pengawasan obat di apotek dan upaya mewujudkan sistem pengawasan obat di apotek yang efektif melalui harmonisasi regulasi.Kata Kunci: Farmasi; Pengawasan Farmasi; Kewenangan Pemerintah